2022
DOI: 10.3389/fpsyg.2022.911427
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Factors of Employee Agility Using Enterprise Social Media: The Moderating Role of Innovation Culture

Abstract: This study aims to create a research model that examines how employee agility is affected by enterprise social media usage (ESMU), and to discuss the moderating role of innovation culture in communication quality, trust, and employee agility using the relational capital theory. Data of 477 Chinese employees from different companies were collected in this study for analysis, and the hypotheses developed were examined. The purpose of this study was to explore the influence mechanism that propels employees’ ESMU,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 108 publications
(164 reference statements)
2
19
0
Order By: Relevance
“…In terms of positive effects, the effect on employee agility was added. Zhang et al [ 90 ] concluded that this behavior influenced employee agility through the moderation of innovation culture. Wei et al [ 91 ] argued that this behavior increases employee agility through meta-knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of positive effects, the effect on employee agility was added. Zhang et al [ 90 ] concluded that this behavior influenced employee agility through the moderation of innovation culture. Wei et al [ 91 ] argued that this behavior increases employee agility through meta-knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the positive moderating effect of task uncertainty on the relationship between social media use and job performance proposed by Lee and Lee [ 116 ] and in line with the task ambiguity mentioned above, some scholars have provided their own insights in terms of employees’ own factors, such as the effect of positive regulation of job expertise on employee agility [ 92 ], the effect of positive regulation of promotion on employee psychological transition, the effect of negative regulation of defense on employee psychological overload [ 114 ], and the effect of negative regulation of work stress on employee agility [ 92 , 117 ]. In terms of work situation factors, Zhang et al [ 90 ] and Ma et al [ 118 ] emphasized the moderating effect of organizational innovation culture on employee social capital, and Oksa et al [ 119 ] explored the moderating effect of COVID-19 on employee work engagement. Wei et al [ 91 ] argued that digital fluency in the organizational environment enhances employee agility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction and background HR Blog system is one of the social technology systems that organisations adopt for employees' use in the workplace (Kauschinger et al, 2022;Zhang et al, 2022;Yousaf et al, 2022;van Zoonen et al, 2022;Behl et al, 2022aBehl et al, , 2022bPandey et al, 2021;Labban and Bizzi, 2022;Mohiya, 2019;Oksa et al, 2021;Kwayu et al, 2021;Bizzi, 2020;Chen and Wei, 2020;Lee, 2020;Di Tommaso et al, 2020;Berraies et al, 2020;Pitafi et al, 2020;Men et al, 2020). However, some researchers posit that employers are struggling to make employees trust and use the system (Zhang et al, 2022;Nilasari, 2020;Berraies et al, 2020;Kauschinger et al, 2022;Yousaf et al, 2022;Cummings, 2017;Chin et al, 2015). Numerous researchers have emphasised the importance of making employees use HR Blog (Zhang et al, 2022;Nilasari, 2020;Berraies et al, 2020;Kauschinger et al, 2022;Yousaf et al, 2022;Chin et al, 2015;Gonzalez et al, 2013;Van Osch and Coursaris, 2013;Turban et al, 2011;Sangwan et al, 2009).…”
mentioning
confidence: 99%
“…However, the main issue in the literature in terms of employees' trust in HR Blog is that there is a clear neglect of how the trust occurs in HR Blog and, most importantly, what the root causes of it are. Zhang et al (2022), Nilasari (2020) and Berraies et al (2020) posit that trust is a key determinant of participation in an HR Blog platform. Zhang et al (2022) and Nilasari (2020) found that an employer's trust is an important factor in making HR Blog use successful in the workplace.…”
mentioning
confidence: 99%